Competence approach as a methodological basis of formation of the leadership qualities of the personality - Черевко, О. В. (Scientific notes of the pedagogical department, 2018)
The urgency of the problem is argued by the necessity of creating a viable system of continuous education for reaching citizens of high educational levels, ensuring opportunities for constant spiritual perfection of the individual, the formation of intellectual and cultural potential as the highest value of the nation. It is emphasized that it becomes possible under the condition of radical updating and restructuring of the educational system on the basis of a competent approach. Purpose of the article is to determine the competence approach as a methodological basis for the formation of leadership qualities of the personality. Results. The description of the key concept – «competence» is represented in the article. The directions of its research in the activity of international organizations and domestic scientists are shown. Re-thinking the role of pedagogy as a science was highlighted. Its description is given as dynamic, dialectical, and flexible science. Originality. The connection between concepts of competent approach and leadership is analyzed. The basic leadership qualities that determine the personality of a new era are substantiated. The competence approach as a methodological basis for the formation of leadership qualities of the personality is determined. It is proved that leadership qualities can be produced in the educational process. In the article the list of key leadership qualities are represented. Conclusion. It is stressed that the new generation should become a leader in the path of social transformation. The ability to transform will be those representatives of human society who will lead, confidently overcome obstacles. They will show at the same time high motivation, cognition, behavioral skills, value-semantic education, the ability to emotionally-volitional regulation.